PERAN BIMBINGAN DAN KONSELING DALAM PENCEGAHAN DAN MENANGGULANGI HIV-AIDS - Santi Noor Rahmah; Rahman; Octa Nabilla Kuswandi; Nabila Novarianti; Uci Oktawati; R.A Rahmatu A'liyah; Syska Purnama Sari (CV. Kalimasada Group, 2025)
HIV/AIDS is a global health issue that affects not only physical health but also psychological, social, and emotional aspects of individuals. The role of guidance and counseling is crucial in the prevention and management of HIV/AIDS through educational, preventive, and curative approaches. Guidance and counseling services contribute to providing accurate information about HIV/AIDS, shaping healthy attitudes and behaviors, and helping individuals develop responsible decision-making skills. In addition, counseling services offer psychological support for individuals at risk or living with HIV/AIDS to help them accept their condition, reduce stigma, and improve their quality of life. Therefore, guidance and counseling serve as an important strategy in reducing the transmission of HIV/AIDS and enhancing individual and community well-being.